Keberpihakan Terhadap Orang Miskin Sebagai Tindakan Kenosis - Agustinus Daryanto (Litbang STFT Widya Sasana Malang, 2022)
Abstract: This paper aims to show that preferential option for the poor is an act of kenosis. Kenosis is often understood as an act of self-emptying. However, in the contemporary context a question arises regarding the absence of human agency and human freedom in the face of the act of self-emptying. Marxism, for example, criticizes Christian morality based on this kind of kenosis as an opium for the poor. On the other hand, liberation theology sometimes places too much emphasis on agency and freedom, so that it is accused of being a Marxist. Pope Francis said that preferential option for the poor is more of a theological category rather than a sociological, philosophical or political one. Through Hans Urs von Balthasar's kenosis theology, the vision of preferential option for the poor has a new meaning. This means that, one must not fall to one of the extremes, either as a passive act or an overly aggressive action. Freedom and agency are understood in a new way in terms of Divine love as seen in the Trinitarian love relationship. The struggle for justice and the suffering of the poor empowers the poor as concrete historical subjects. They are not passive objects deceived by self-emptying. Abstrak: Tulisan ini bertujuan untuk menunjukkan bahwa keberpihakan terhadap orang miskin merupakan sebuah tindakan kenosis. Kenosis sering dipahami sebagai tindakan pengosongan diri. Namun, dalam konteks kontemporer muncul pertanyaan mengenai hilangnya agensi dan kebebasan manusia di hadapan tindakan pengosongan diri. Marxisme misalnya mengkritik moralitas Kristiani yang didasarkan pada kenosis ini sebagai candu bagi orang miskin. Di sisi lain teologi pembebasan kadangkala terlalu menekankan agensi dan kebebasan, sehingga dituduh sebagai Marxis. Paus Fransiskus mengatakan bahwa keberpihakan terhadap orang miskin lebih merupakan kategori teologis daripada sosiologis, filosofis, maupun politis. Melalui teologi kenosis Hans Urs von Balthasar, visi keberpihakan terhadap orang miskin mendapatkan makna baru. Artinya, tidak jatuh pada salah satu ekstrem, baik sebagai tindakan pasif maupun tindakan yang terlalu agresif. Kebebasan dan agensi dipahami secara baru berdasarkan ukuran cinta Ilahi sebagaimana nampak dalam relasi cinta Trinitaris. Perjuangan terhadap keadilan dan penderitaan orang miskin memberdayakan orang miskin sebagai subyek sejarah yang konkrit. Mereka bukan objek pasif yang diperdaya oleh pengososan diri.